Advanced Hybrid Epoxy Nanocomposite Coatings with Nanoclay and Multi-Walled Carbon Nanotubes for Enhanced Flame Retardancy - Nguyen, Tuan Anh; Ngo, Thuy Van (Trends in Sciences, 2025)
This study investigates the effect of incorporating nanoclay I.30E and multi-walled carbon nanotubes into epoxy coatings to enhance mechanical properties and flame retardancy. X-ray diffraction (XRD) analysis indicates that with the addition of 5 % nanoclay and 0.5 % multi-walled carbon nanotubes, the nanoclay exhibits the best dispersion, with an expanded d-spacing of 27.59 Å, suggesting intercalation and a tendency toward complete exfoliation. Thermogravimetric analysis (TGA) confirms that this optimized sample demonstrates the highest thermal stability, with a decomposition temperature approximately 40 °C higher than pure epoxy, reaching ~350 °C, and the highest residual char at 500 °C, proving the protective effect of the nanofillers. Scanning electron microscopy (SEM) analysis reveals that this combination enhances the dispersion of nanoclay and carbon nanotubes within the epoxy matrix, thereby improving the mechanical properties of the material. The tensile strength and impact resistance of the optimized sample increase by 35 and 27 %, respectively, compared to pure epoxy. HIGHLIGHTS A novel hybrid epoxy nanocomposite coating was developed using nanoclay I.30E and multi-walled carbon nanotubes (MWCNTs). Optimal composition (5 wt% nanoclay and 0.5 wt% MWCNTs) achieved the best nanoclay dispersion with an expanded d-spacing of 27.59 Å. Thermal stability improved significantly with decomposition temperature ~40 °C higher and highest char residue at 500 °C. Tensile strength and impact resistance were enhanced by 35 and 27 %, respectively, compared to pure epoxy. SEM analysis confirmed uniform dispersion of nanofillers, contributing to improved mechanical and flame-retardant performance. GRAPHICAL ABSTRACT